The Implementation of Curriculum Management in Enhancing Educational Capacity at Dayah MUDI II Samalanga - Yani, Ahmad (Scientific Journal for Nation Building, 2025)
Dayah MUDI II Samalanga is an Islamic educational institution that integrates Islamic values into its learning processes. One of the key factors in improving the quality of education in this dayah is the implementation of effective and sustainable curriculum management. This study aims to analyze how curriculum management is applied to enhance educational quality. The research employs a qualitative approach through observation, interviews, and document analysis. The findings reveal that a structured and adaptive curriculum management system plays a significant role in improving learning quality, student competence, and the relevance of education to contemporary developments. Curriculum planning is based on a needs analysis, particularly in preparing competent future educators. The implementation process preserves traditional dayah practices while applying contextual learning strategies. Curriculum development is carried out through deliberation involving the leadership, teungku (religious scholars), and dayah administrators. To achieve optimal educational improvement, adequate resource support and increased student awareness in the pursuit of knowledge are essential.